(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2016)
A problem encountered in plant breeding process to determine bean color quality of fine-flavor cocoa is a long selection period. Preliminary results indicated that the fine-flavor cocoa has a low color reflectance than bulk cocoa. The objective of this study is to find more applicable and easier method to do the early detection of fine-flavor cocoa on the breeding population. Detection of the leaf color haracteristics was done by chromatographic and spectrophotometry analysis. hromatographic analysis was carried out in Kaliwining Experimental Station, Indonesian Coffee and Cocoa Research Institute using complete random design consisted of two types of cocoa; fine-flavor (10 clones) and bulk cocoa (10 clones). pectrophotometric analysis was conducted at Ma Chung University, Malang, East Java. Four clones of bulk cocoa and six clones of fine flavor cocoa were used in this analysis. The results of the study showed that the flush color characteristics of the fine-flavor cocoa were different from the bulk cocoa characteristics as shown by the differences in the value of L*, b* and anthocyanin content. Flush characteristic s of the fine-flavor cocoa had brighter color, more toward green with higher yellow level, while the bulk cocoa had darker flush, red and lower yellow level. The color parameter of L* and b* had a higher genetic variation compared with the environment variation. However, the parameter a* had a higher environmental variation compared with genetic variation. Grouping of fine-flavor cocoa and bulk cocoa could be done through the detection of flush anthocyanin content, when tendency of flush anthocyanin content on fine-flavor cocoa was lower than bulk cocoa. The detection of flush color particularly L* and b* parameters through hromatographic analysis and anthocyanin content through spectrophotometric analysis may be used as a criteria for selection the fine flavor cocoa on seedling phase.